Pengaruh Pemberian Lampu LED Terhadap Karakter Pertumbuhan Beberapa Tanaman Microgreens Famili Brassica Sp - Farokha Tunnisa; Yayu Sri Rahayu; Nurcahyo Widyodaru Saputro (JURNAL PERTANIAN, 2026)
Limited land and increasing awareness of healthy lifestyles encourage the application of efficient cultivation methods such as microgreens, which are young shoots of vegetables that are rich in nutrients and are harvested in 7–21 days. This study aims to examine the influence of the type of LED lamp on the growth of several microgreens of the Brassicaceae family. The research was carried out using a split plot Group Random Design (RAK). The main tile factor is LED light (6 levels: inner control, outdoor control, blue LED, red LED, red-blue LED, and white LED), while the subplot consists of three types of microgreens (cabbage, turnips, and broccoli), with two replicas (36 experimental units). The data was analyzed using a 5% variety analysis, followed by the Duncan Multiple Range Test (DMRT) if there were any real differences. The results showed that there was no interaction between LED lights and plant types on plant height at 4, 7, and 10 days after planting (dap), rate of increase in number of leaves, and relative growth rate. Separately, red LEDs produce the highest plants, blue LEDs increase the number of leaves, and sunlight provides the highest LPR. Horseradish plants show the best growth compared to broccoli and flower cabbage.